Orde ab Chao Method for Disruptive Innovations Creation (With COVID-19 Pandemic Case Application) - Likar, Borut; Trcek, Denis (Frontiers in Psychology, 2021)
This paper introduces a novel method for the creation of ideas for disruptive innovations. It provides an application of innovation management techniques to specifics of disruptive technologies, which stand behind the Industry 4.0 (and Society 4.0) changes that are taking place at present. Centered around the Ordo ab Chao technique, the paper presents how contemporary disruptive technologies can attain reflections in the complex creative process that has to lead to disruptive ideas and innovations. Quite some innovative thinking techniques already exist. However, they fail to place emphasis on creation of ideas that are tied to emerging disruptive technologies so as to further deploy them in a focused, yet innovative manner. Hence, this paper presents an effective technique that facilitates creation of disruptive ideas with a focused potential for real-life implementations. Practical application of the method related to challenges in higher education processes amid the COVID-19 pandemic is also demonstrated. Based on the understanding of existing disruptive technologies, the technique is used for the adaptation and improvements of distance-learning processes to further add value for students and our society in general. In brief, the Ordo ab Chao technique is a promising tool for systematic development of disruptive solutions, representing a creative synergy between cutting-edge technologies and innovation management approaches.